Fatty acid composition of lipid fractions in Parma ham obtained from pigs fed on different levels of vitamin E (alpha-tochopherol acetate) - Lo Fiego D.P.; Santoro P.; Macchioni P.; Minelli G. (Tradition and innovation in Mediterranean pig production, 2000)
The fatty acid composition of intramuscular lipids and adipose covering tissue was studied on 45 Parma hams obtained from Duroc by Cotswold heavy pigs (carcass weight 129.5 plus minus 8.0 kg). The animals were fed on a diet supplemented with either 8 ppm of vitamin E for 95 days (C) or 200 ppm for 65 days (T1) or 200 ppm for 95 days (T2) and slaughtered at about 160 kg liveweight. Total intramuscular lipids, (3.38 per cent), contained, on average, 35.6 per cent of saturated (SFA), 48.5 per cent monounsaturated (MUFA) and 15.9 per cent polyunsaturated (PUFA) fatty acids. The dietary level of vitamin E had no statistically significant effect on fatty acid composition of total intramuscular lipids, although the animals of groups T1 and T2 showed lipids tendentially richer in PUFA. The neutral fraction of intramuscular lipids comprising 35.5 per cent of SFA, 56.5 per cent MUFA and 8.0 per cent PUFA, was lower in PUFA in hams from C group (P less than 0.05).
4. International Symposium on Mediterranean Pig, 1998/11/26-28, Evora (Portugal)